Superior segmental optic nerve hypoplasia accompanied by progressive normal-tension glaucoma - Yamazaki Y (Dove Medical Press, 2012)
Yoshio Yamazaki, Fukuko HayamizuDepartment of Ophthalmology, Division of Visual Science, Nihon University School of Medicine, Tokyo, JapanAbstract: This is the first case report of a superior segmental optic hypoplasia (SSOH) combined with normal-tension glaucoma accompanied by a progressive glaucomatous visual field defect. A 40-year-old man, incidentally diagnosed as having bilateral SSOH, had disc hemorrhage associated with expansion of the width of a retinal nerve fiber layer defect and deterioration of a visual field defect in the right eye during the follow-up period. His left eye showed a stable visual field. The diurnal variation in intraocular pressure (IOP) showed a higher mean IOP in his right eye compared with his left eye, although both IOPs remained under 21 mmHg.Keywords: visual field defects, disc hemorrhage, retinal nerve fiber layer defect, intraocular pressure